1999
DOI: 10.1046/j.1525-1470.1999.99012.x
|View full text |Cite
|
Sign up to set email alerts
|

Granulomatous Cheilitis and Crohn's Disease in a 3‐Year‐Old Boy

Abstract: Granulomatous cheilitis and Crohn's disease are disorders of unknown etiology. There are case reports describing their coincidence and pointing out the necessity of ruling out systemic disorders once the diagnosis of granulomatous cheilitis is made. However, such reports are few and the causal association of both diseases is controversial in the literature. We report the youngest patient so far, a 3-year-old boy, who had granulomatous cheilitis and Crohn's disease simultaneously. This coincidence so early in l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
3

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 22 publications
1
28
0
3
Order By: Relevance
“…Additionally sarcoidosis, infectious processes such as tuberculosis, and Crohn disease are included in this group 1 . It has been suggested that up to 0·5% of patients with Crohn disease will develop GC and its presence either prior to or accompanying initial gastrointestinal manifestations of Crohn disease has been noted 4,6,7 . Although the underlying mechanisms that cause GC remain unclear, it has been suggested that it probably consists of a polyaetiological interplay of environmental exposures and genetic predisposition 1 …”
Section: Conditions Associated With or In The Differential Diagnosismentioning
confidence: 99%
“…Additionally sarcoidosis, infectious processes such as tuberculosis, and Crohn disease are included in this group 1 . It has been suggested that up to 0·5% of patients with Crohn disease will develop GC and its presence either prior to or accompanying initial gastrointestinal manifestations of Crohn disease has been noted 4,6,7 . Although the underlying mechanisms that cause GC remain unclear, it has been suggested that it probably consists of a polyaetiological interplay of environmental exposures and genetic predisposition 1 …”
Section: Conditions Associated With or In The Differential Diagnosismentioning
confidence: 99%
“…605 The etiology is unknown but the syndrome has been considered to be a manifestation of sarcoidosis, 606 a reaction to infection or to foreign material, such as silicates, gold, and mercury, 607 and a delayed hypersensitivity to cow's milk protein or food additives. 279,[615][616][617] The lip sign may predate gastrointestinal symptoms by years. 609 Borrelia burgdorferi has been excluded as an etiological agent, 610 but the DNA of Mycobacterium tuberculosis has been identified by PCR in one case.…”
Section: Melkersson-rosenthal Syndromementioning
confidence: 99%
“…The association of OFG with gastrointestinal CD is well documented, and rates of 10–48% have been reported in various series [1, 12, 13]. In contrast, diagnosis of MRS or OFG in childhood is a rarity: in a recent review, Ziem et al [14]found a mere 32 children and adolescents reported in the literature, only one of whom had concomitant CD [15]. …”
Section: Introductionmentioning
confidence: 99%